KAJIAN ETNOBOTANI PADA TRADISI PERNIKAHAN ADAT KERATON SURAKARTA, PROVINSI JAWA TENGAH - Eka Supriyati (Scripta Biologica, 2018)
Marriage is the emotional bond between man and woman to form a happy family. Marriage tradition including their ceremonial also conducted in areas such as the Keraton Surakarta. The ceremonial in Keraton Surakarta Central Java Province has been known as a basic pattern of tradition marriage by Javanese. Various types of plants are utilized in marriage tradition. The utilization of plants by community in particular areas is studied through the scince of ethnobotay. The purpose of this study is to know the wedding ceremonial tradition of Keraton Surakarta Indonesia in terms of the use of the plants and their meanings. This research used descriptive method with interviews. The sampling used purposive random sampling on servants in Keraton Surakarta and locals near Keraton. The result of the research shows the tradition of Surakarta traditional marriage utilizing various plants around it with a noble and positive meaning. The use of plants at each stage of marriage is different and has defferent meaning.